SYSTEMATIC LITERATURE REVIEW : PENGARUH PENGGUNAAN MEDIA MANIPULATIF TERHADAP KECEMASAN MATEMATIS SISWA - Mutiara septiana, Chen Anaqu; Nindiasari, Hepsi; Pujiastuti, Heni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Mathematics anxiety is one of the main challenges in mathematics learning that can affect students’ engagement and academic performance. This study aims to examine the effect of manipulative media on students’ mathematics anxiety through a Systematic Literature Review (SLR) approach. Data were collected from Google Scholar, SINTA, Garuda, and Scopus, limited to publications from 2020 to 2024, and selected using the PRISMA framework, resulting in 17 relevant articles. The analysis employed content analysis and thematic synthesis to identify patterns across studies. The findings indicate that the use of manipulative media is associated with a reduction in mathematics anxiety, particularly among secondary school students. This reduction occurs through the concretization of abstract concepts, increased student engagement, and the creation of a more supportive learning environment. Both concrete and virtual manipulatives are effective, with a combined approach showing more optimal results. Therefore, manipulative media have the potential to support both cognitive and affective aspects of mathematics learning